First record of Synedropsis roundii (Bacillariophyta, Fragilariaceae) in the Mediterranean region - BLANCO, SAÚL; ROMO, SUSANA; GARCÍA-MURCIA, ANA (Mediterranean Marine Science, 2019)
Populations of the fragilarioid diatom Synedropsis roundii are described from the phytoplankton of the Albufera of Valencia, a large and shallow eutrophic lagoon in the Spanish Mediterranean coast. The specimens collected are described and illustrated with light and scanning electron microscopy. This is the first documented record of this species since its description, and the first illustrated record of the genus in the Mediterranean region. The Albufera lagoon and the type locality of the species (Imboassica Lagoon, SE Brazil) are similar in some ecological features. The ecological and biogeographical implications of this finding are briefly discussed.